O pensar e o fazer de pedagogas no caps - Góis, Adriano Lucena de (Universidade Federal Rural do Semi-Árido, 2019)
This work is a master's thesis and it is a research that addresses the pedagogical practice of the day-to-day in the Center for Psychosocial Care (CAPS). The pedagogue has long been a professional trained to work on existing educational processes within the school. But, this reality is changing and today there are several fields of action in and out of school, one of them being mental health and psychosocial care. Thus, the general objective was to analyze the activity developed by the pedagogue in the CAPS in cities of the state of Rio Grande do Norte. And, as specific objectives to map the activities developed by the pedagogue in the CAPS potiguares; To analyze how the pedagogue perceives himself as a professional in psychosocial attention. It also investigates the life trajectory of the research participants until their arrival at CAPS. Methods of qualitative research were used, with data production through an interview with semi-structured script, in which the research participants were asked about their work. This moment of interview took place in two moments, one that started with the subjectivity of the pedagogues and another that dealt with aspects of their actions in the CAPS. Two of the pedagogues that participated in the psychosocial care at CAPS in the State of Rio Grande do Norte were participants of the study. The research is based on the theories of different authors that compose the fields of mental health, education, education and health, the activities of the pedagogue in non-school space, such as. The results point to the many and can be said important activities developed by the pedagogue in the CAPS, such as painting workshops, insertion and stimulation to the process of Teaching and Learning, among others. Although the pedagogue faces a series of difficulties facing the effectiveness of his actions in mental health. The little structuring of the CAPS constitutes an obstacle, or difficult of the practices of this professional. Despite the lack of training directed at the psychosocial field, what the pedagogue does today in the CAPS has been relevant to the need of the subjects in psychic suffering. Through the moment of data collection, it was possible to perceive that the pedagogues perceive their work as meaningful in regard to mental health care, not only in the CAPS, but as an integral part of the psychosocial care network in Rio Grande do Norte
Keywords: Pedagogia; Saúde mental; CAPS; Pedagogy; Mental health; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES